2019
DOI: 10.3390/v11090849
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells (DCs) as “Fire Accelerants” of Hantaviral Pathogenesis

Abstract: Hantaviruses are widespread zoonotic pathogens found around the globe. Depending on their geographical location, hantaviruses can cause two human syndromes, haemorrhagic fever with renal syndrome (HFRS) or hantavirus pulmonary syndrome (HPS). HPS and HFRS have many commonalities amongst which excessive activation of immune cells is a prominent feature. Hantaviruses replicate in endothelial cells (ECs), the major battlefield of hantavirus-induced pathogenesis, without causing cytopathic effects. This indicates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 71 publications
1
13
0
1
Order By: Relevance
“…This suggests that hantaviral pathogenicity is linked to the MPS and β2 integrins. In accordance, several pathogenic hantavirus species (HTNV, PUUV, and ANDV) have previously been demonstrated to productively infect human DCs in vitro (Raftery et al, 2002a;Marsac et al, 2011;Scholz et al, 2017;Schonrich and Raftery, 2019). Previous studies also reported in vitro infection of primary monocytes (Nagai et al, 1985;Temonen et al, 1993;Scholz et al, 2017) or a monocytic cell line (Markotic et al, 2007) with pathogenic hantavirus species.…”
Section: Introductionsupporting
confidence: 60%
“…This suggests that hantaviral pathogenicity is linked to the MPS and β2 integrins. In accordance, several pathogenic hantavirus species (HTNV, PUUV, and ANDV) have previously been demonstrated to productively infect human DCs in vitro (Raftery et al, 2002a;Marsac et al, 2011;Scholz et al, 2017;Schonrich and Raftery, 2019). Previous studies also reported in vitro infection of primary monocytes (Nagai et al, 1985;Temonen et al, 1993;Scholz et al, 2017) or a monocytic cell line (Markotic et al, 2007) with pathogenic hantavirus species.…”
Section: Introductionsupporting
confidence: 60%
“…47 These findings indicate that the activation of the immune response mediated by infected DCs could contribute to the pathogenesis during viral infection. 34 Moreover, analyses of human tissue samples from ANDV fatal cases and infected wild Oligoryzomys longicaudatus rodents identified ANDV in alveolar macrophages and submandibular glands. 91 It has been proposed that replication in human salivary glands and expectoration of alveolar macrophages could contribute to personto-person transmission.…”
Section: Dendritic Cells and Macrophagesmentioning
confidence: 99%
“…64 The upregulation of these chemo-attractant cytokines might be responsible for the recruitment of hantavirus-specific immune cells and extensive bystander activation of innate and cytotoxic cells that destroy ECs. 34 This scenario, combined with the cell-to-cell junction disruption, could promote platelet migration at the injury site, with the consequent thrombocytopenia commonly found in hantavirus disease. 56,66 Additionally, alterations between platelets and their ligands are reported during hantavirus infection, with high levels of fibrinogen and von Willebrand factor (VWF) in the acute stage of NE, 67 both directly involved in the initial steps of clot formation.…”
Section: Hantavirus-caused Diseases: Hantavirus Cardiopulmonary Syndrome and Haemorrhagic Fever With Renal Syndromementioning
confidence: 99%
See 2 more Smart Citations